Geochemical processes in Kandi Basin, Benin, West Africa: A combined hydrochemistry and stable isotopes approach. (22nd May 2015) - Kpegli, Kodjo Apelete Raoul; Alassane, Abdoukarim; Trabelsi, Rim; Zouari, Kamel; Boukari, Moussa; Mama, Daouda; Dovonon, Firmin Leonce; Yoxi, Yede Victor; Toro-Espitia, Luis Eduardo
Abstract: Detailed hydrochemical and stable isotopic data of surface and groundwater were used to understand the geochemical processes occurring in the Kandi basin in Benin. Hydrochemical investigations show that waters in this basin are of low mineralization, with values of Total Dissolved Solids (TDS) generally less than 1200 mg/L. Water types in the basin are HCO3 –Mg, HCO3 –Na, Cl–Na, HCO3 –Ca, Cl–Ca and most fall in mixture water type (i.e. HCO3 –Mixe and Cl–NO3 –Mixe). The mineralization is governed essentially by the dissolution of dolomite, calcite, aragonite, and magnesite, but not cation exchange reactions. The stable isotope approach underlined the interchange phenomenon between aquifers in the basin, direct recharge of aquifers by surface waters in some areas, and recharge of aquifers by modern precipitation, which influence the groundwater geochemistry in the basin. Anthropic origin of nitrates is underlined by stable isotopes.